Preparation method of carbon nanotube reinforced hard alloy

By preparing MWCNTs/Ni powder material and ball milling and sintering with WC-8Co carbide powder, the problem of insufficient strength and toughness of traditional carbide is solved, and the high hardness and toughness of carbide is enhanced, and the life is extended.

CN119287199AInactive Publication Date: 2025-01-10NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411487074.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cemented carbides have problems that are difficult to solve in the problems of insufficient strength and toughness, poor wear resistance and short life, especially in the use of tool materials, which affects processing efficiency and workpiece quality.

Method used

By preparing MWCNTs/Ni powder materials, including purification, sensitization, activation and electroless Ni treatment, the surfactivity and compatibility of carbon nanotubes are improved and ball milled and sintered with WC-8Co carbide powder. Enhance the dispersion and binding force of carbon nanotubes in alloys.

Benefits of technology

The uniform dispersion and high binding force of MWCNTs in cemented carbide is achieved, which inhibits the growth of WC grains, improves the hardness and toughness of cemented carbide, enhances its mechanical properties, and extends its life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287199A_ABST
    Figure CN119287199A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hard alloy preparation methods, and discloses a carbon nanotube reinforced hard alloy preparation method which comprises the following steps: S1, preparing an MWCNTs / Ni powder material; s2, the MWCNTs / Ni powder material is added into absolute ethyl alcohol dissolved with JCCADS, and after ultrasonic oscillation, centrifugal sedimentation and filtering are conducted, an MWCNTs / Ni absolute ethyl alcohol dispersion system is obtained; and S3, the MWCNTs / Ni absolute ethyl alcohol dispersion system is added into the WC-8Co hard alloy powder for ball milling. According to the preparation method of the carbon nanotube reinforced hard alloy, after vacuum sintering, MWCNTs / Ni still exists in the WC-8Co alloy, movement of a primary interface is inhibited, the effects of inhibiting WC grain growth and refining WC grains are achieved, the bonding strength of the MWCNTs / Ni and a WC-8Co alloy matrix is high, and the excellent mechanical property of the carbon nanotube can be played to enhance the performance of the hard alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide preparation methods, in particular to a method for preparing a carbon nanotube-reinforced cemented carbide. Background Art

[0002] Cemented carbide is known as the "tooth of industry" and has a series of excellent properties, such as high hardness, good red hardness, wear resistance and corrosion resistance. It is usually prepared by adding metal binders (such as Co, Ni, Fe, etc.) to high-hardness metal carbides (such as WC, TiC, TaC, etc.) through powder metallurgy. However, it also has certain disadvantages. For example, insufficient strength and toughness has always been a problem that is difficult to solve for traditional cemented carbide. When used as a tool material, it often suffers from problems such as chipping, poor wear resistance, and short life due to insufficient strength and toughness, affecting processing efficiency and workpiece quality, such as WC-based cemented carbide (WC-Co).

[0003] Therefore, it is of great significance to prepare cemented carbide with high hardness and high toughness.

[0004] Carbon nanotubes (CNTs) are one-dimensional nanomaterials with an interconnected hexagonal structure. They are light in weight, high in strength, toughness and elastic modulus, and have many mechanical properties superior to ordinary materials. They have been a hot topic of scientific research since their discovery. Doping carbon nanotubes in cemented carbide and taking advantage of the strong and tough characteristics of CNTs and using CNTs as the reinforcing phase of cemented carbide can not only ensure the high hardness of the material, but also improve the toughness of the material.

[0005] For example, in the invention patent with the Chinese patent announcement number: CN115612906B, a carbon nanotube-alumina modified cemented carbide is provided, which includes the following components (by weight): 90-98 parts of WC powder; 3-8 parts of Co powder; 0.5-2 parts of Ni powder; 0.1-0.5 parts of carbon nanotubes; 0.5-1.5 parts of alumina; 0.05-0.2 parts of yttrium oxide. In the above cemented carbide, although the strength and toughness of the cemented carbide are significantly improved by adding carbon nanotubes, in actual application, we found that it still has certain areas that can be optimized, such as: The above CNTs have not been surface treated, and when used as a reinforcement phase, their bonding strength with the matrix is ​​relatively poor, and their uniformity of dispersion in the alloy material is also relatively poor. Summary of the invention

[0006] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention provides a method for preparing a carbon nanotube-reinforced cemented carbide, which has the advantages of uniform dispersion of MWCNTs and good interface bonding strength with the cemented carbide substrate.

[0007] (II) Technical solution In order to achieve the purpose of uniform dispersion of MWCNTs and good interface bonding strength with cemented carbide substrate, the present invention provides the following technical solution: a method for preparing carbon nanotube-reinforced cemented carbide, comprising the following steps: S1. preparing MWCNTs / Ni powder material; S2, adding MWCNTs / Ni powder material into anhydrous ethanol containing JCCADS, and obtaining MWCNTs / Ni anhydrous ethanol dispersion system after ultrasonic oscillation, centrifugal sedimentation and filtration; S3, adding the MWCNTs / Ni anhydrous ethanol dispersion system to WC-8Co cemented carbide powder for ball milling; S4, separating the grinding balls and the slurry by sieving, and vacuum drying the slurry to obtain a mixed powder; S5. Pressing and sintering the mixed powder to obtain WC-8Co cemented carbide.

[0008] As a preferred technical solution of the present invention, in step S1, preparing MWCNTs / Ni powder material comprises the following steps: S101, purifying MWCNTs using high concentration HNO3 solution; S102, putting the purified MWCNTs obtained in step S101 into a 10 g / L SnCl2 aqueous solution at pH=1, stirring, ultrasonically treating, washing, filtering and drying to obtain sensitized MWCNTs; S103, putting the sensitized MWCNTs into an activation solution, stirring, ultrasonically treating, washing, filtering and drying to obtain activated MWCNTs; S104, placing the activated MWCNTs obtained in step S103 into a chemical Ni plating solution, and plating for 100 minutes at a constant temperature; MWCNTs / Ni is separated from the aqueous solution and dried to obtain MWCNTs / Ni powder material.

[0009] As a preferred technical solution of the present invention, in step S104, (NH4)2SO4 is used to adjust the pH of the plating solution to 8.1; Surfactant C is also added to the chemical Ni plating solution. 18 H 29 NaO3S, dosage is 0.1g / L.

[0010] As a preferred technical solution of the present invention, in step S104, MWCNTs / Ni is repeatedly washed with deionized water until it becomes neutral, and the MWCNTs / Ni and the aqueous solution are separated by a combination of centrifugation and filtration; The MWCNTs / Ni was completely dried at 170°C for 7 h.

[0011] As a preferred technical solution of the present invention, in step S101, MWCNTs and high concentration HNO3 solution are added to a round-bottom flask, heated to 120°C in a condensation reflux device, and kept warm for 12 hours; The treated MWCNTs are then repeatedly washed with deionized water, filtered and separated after washing, and completely dried in a vacuum drying oven to obtain purified MWCNTs.

[0012] As a preferred technical solution of the present invention, in step S103, the activation solution is a mixed solution with a pH value of 1, and the solution composition is a PdCl2 solution with a concentration of 0.5 g / L and a H3BO3 solution with a concentration of 10 g / L; As a preferred technical solution of the present invention, the amount of dispersant added to the anhydrous ethanol in which JCCADS is dissolved is 0.2 times the weight of the carbon nanotubes.

[0013] As a preferred technical solution of the present invention, in step S3, the addition amount of MWCNTs / Ni is 0.2-1% by weight, and the rest includes: 0.6% by weight of VC, 0.4% by weight of LC-38, 8% by weight of Co, and the balance is WC.

[0014] As a preferred technical solution of the present invention, in step S5, LC-38 is mixed into the mixed powder before pressing.

[0015] As a preferred technical solution of the present invention, in step S5, the pressing pressure is 210 MPa.

[0016] (III) Beneficial effects Compared with the prior art, the present invention provides a method for preparing carbon nanotube-reinforced cemented carbide, which has the following beneficial effects: 1. The method for preparing carbon nanotube-reinforced cemented carbide greatly reduces the surface activation energy of MWCNTs after Ni plating, and enhances their activity, thereby enhancing their dispersibility and improving their compatibility with other metals or compounds. In the application of MWCNTs-reinforced cemented carbide materials, the MWCNTs can be dispersed more evenly in the alloy material, and the wettability and interface bonding strength between the MWCNTs and the cemented carbide substrate can be improved.

[0017] 2. The method for preparing carbon nanotube-reinforced cemented carbide, after three steps of purification, sensitization and activation, the MWCNTs have good surface activity and can be further treated with chemical Ni plating; the improvement of this surface activity is conducive to the interaction between MWCNTs and nickel ions, thereby achieving Ni deposition and ultimately preparing MWCNTs / Ni with excellent performance.

[0018] 3. In the preparation method of cemented carbide reinforced by carbon nanotubes, MWCNTs / Ni still exists in the WC-8Co alloy after vacuum sintering, which inhibits the movement of the primary interface, plays a role in inhibiting the growth of WC grains and refining WC grains. In addition, the bonding strength between MWCNTs / Ni and the WC-8Co alloy matrix is ​​relatively high, and the excellent mechanical properties of carbon nanotubes can be brought into play to enhance the performance of cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 SEM characterization photos of purchased MWCNTs, purified MWCNTs and MWCNTs / Ni; Figure 2 Comparison diagram of MWCNTs / Ni before and after heat treatment; Figure 3 This is a sintering temperature curve diagram of the present invention; Figure 4 The SEM characterization photos of WC-8Co alloy powders with different MWCNTs / Ni contents of the present invention; Figure 5 This is the SEM characterization photo of the existence state of MWCNTs / Ni in the mixed powder; Figure 6 WC-8Co alloy grains with different MWCNTs / Ni contents; Figure 7 Statistics of grain size of WC-8Co alloy with different MWCNTs / Ni contents; Figure 8 The effect of carbon tube content on hardness and toughness; Fig. 9 The effect of carbon tube content on coercivity and grain size; Fig.10 The influence of carbon tube content on density and compactness; Fig.11 The effect of carbon tube content on bending strength. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example: See also Figure 1-11 , a method for preparing a carbon nanotube-reinforced cemented carbide, comprising the following steps: Step 1, preparing MWCNTs / Ni powder material; After Ni plating, the surface activation energy of MWCNTs is greatly reduced and the activity is enhanced, so its dispersibility is enhanced and its compatibility with other metals or compounds is also improved. In the application of MWCNTs to reinforce cemented carbide materials, MWCNTs can be dispersed more evenly in the alloy material, and the wettability and interfacial bonding strength between MWCNTs and cemented carbide substrate can be improved.

[0022] The wall surface of MWCNTs is smooth and stable, the CC bond is stable, and it has no catalytic properties. In addition, the surface activity of MWCNTs is low and it is difficult to be infiltrated by metals or compounds. In order to overcome these limitations, in this embodiment, surface modification is selected to improve its surface activity and dispersibility. In addition, commercially available MWCNTs usually contain more impurities, which can reduce the purity of MWCNTs and thus affect their performance and applications; Therefore, in this embodiment, the preparation of MWCNTs / Ni powder material specifically includes four steps of purification, sensitization, activation and plating: purification: First, a high concentration HNO3 solution was used for oxidation treatment. The purpose of this step is to introduce oxygen functional groups such as -COOH through strong acid treatment to change the surface properties of MWCNTs and improve their dispersibility; during the treatment process, about 300 mL of high concentration HNO3 solution and 1 g of MWCNTs were added to a round-bottom flask, and heated to 120°C under a condensation reflux device and kept warm for 12 hours. Such treatment conditions can accelerate the reaction; Afterwards, the treated MWCNTs need to be repeatedly washed and filtered with deionized water to remove impurities such as HNO3 remaining on the surface and adjust the pH of the solution to a pH close to 7; then, the washed MWCNTs are completely dried in a vacuum drying oven to remove residual moisture.

[0023] After treatment, most of the impurities in MWCNTs are removed, and oxygen functional groups are connected, which increases the surface active sites of MWCNTs and improves the reaction activity so that they can play a role in the subsequent chemical plating process; In addition, the treated MWCNTs can also be well dispersed in ethanol, which is very important for many applications because ethanol is a common mixing medium; and the well-dispersed MWCNTs can be better mixed with other substances, ultimately improving the performance of the composite material; The -COOH on the wall of the purified carbon nanotubes can serve as a catalytic site to provide a catalytic effect for the chemical plating process; in application, Ni needs to be deposited on the surface of MWCNTs to change its properties. Therefore, the -COOH on the wall of the treated MWCNTs can serve as a catalytic site to promote the subsequent chemical plating process, thereby achieving the goal.

[0024] Sensitization: At room temperature, the purified MWCNTs were placed in a 10 g / L SnCl2 aqueous solution with a pH of 1, first mechanically stirred for 30 min, then ultrasonically treated for 90 min using an ultrasonic cell crusher, and finally washed, filtered, and dried to obtain sensitized MWCNTs.

[0025] activation: The sensitized MWCNTs were put into the activation solution, mechanically stirred for 30 minutes, ultrasonically dispersed for 90 minutes, then washed, filtered and dried to obtain the activated MWCNTs; the activation solution was a mixed solution with a pH of 1, and the solution composition was a PdCl2 solution with a concentration of 0.5 g / L and a H3BO3 solution with a concentration of 10 g / L.

[0026] During the purification, sensitization and activation process, ultrasonic dispersion and washing and filtration are necessary. MWCNTs tend to have high agglomeration and are easy to form clumps, which reduces their dispersibility. Ultrasonic dispersion can effectively break the agglomeration between MWCNTs and make them better dispersed in the solution. After the treatment, there may be impurities in the solution, such as generated oxides, unreacted acids, etc. By using deionized water for washing and filtration, these impurities can be effectively removed, so that the MWCNTs can be thoroughly cleaned.

[0027] After the three steps of purification, sensitization and activation, MWCNTs have good surface activity and can be further treated with chemical Ni plating. This increase in surface activity will help the interaction between MWCNTs and nickel ions, thereby achieving Ni deposition and ultimately preparing MWCNTs / Ni with excellent performance.

[0028] After MWCNTs were purified by high concentration HNO3 solution, functional groups were grafted on the surface. During the sensitization process, SnCl2 was hydrolyzed to generate Sn(OH)Cl which is slightly soluble in water. (s) Particles, the hydrolysis equation is: SnCl2+H2O→Sn(OH)Cl (s) +HCl These particles are adsorbed in the form of bonds on the surface of carbon nanotubes where the functional groups are dense. These particles are positively charged, so they repel each other, which is beneficial to maintain the stability of the solution and reduce the entanglement of MWCNTs and keep them evenly dispersed.

[0029] Nano-Sn(OH)Cl (s) With a loose structure, in the activation solution, Pd + Can easily enter Sn(OH)Cl (s) particles and is Sn 2+ Reduction to Pd atoms, the equation is 2Pd + +Sn 2+ →Sn 4+ +2Pd Pd atoms are deposited on the surface of MWCNTs to form activation points. As a result, some areas on the surface of MWCNTs have strong catalytic activity. It is at these activation points that Ni + It is reduced to Ni atoms and deposited on the surface of MWCNTs. As the chemical plating in the solution continues, the formed Ni coating gradually covers the MWCNTs. At this time, the Ni atoms with good self-catalytic activity replace the Pd atoms and become new activation points, so that the reaction can continue. The Ni coating continues to grow, and the desired Ni coating can be obtained by controlling the plating time.

[0030] In this embodiment, the specific plating method is: put the purified, sensitized and activated MWCNTs into a chemical Ni plating solution, and add an appropriate amount of surfactant C into the plating solution. 18 H 29 NaO3S, the dosage is 0.1g / L. (NH4)2SO4 is used to adjust the pH of the plating solution to 8.1, and the mechanical stirring rate is set to 200r / min under the condition of constant temperature of 25℃, and the plating is carried out for 100min. MWCNTs / Ni is repeatedly washed with deionized water until neutral, and the MWCNTs / Ni and the aqueous solution are separated by a combination of centrifugation and filtration, and the MWCNTs / Ni is kept at a constant temperature of 170℃ for 7h to be completely dried to obtain the MWCNTs / Ni powder material.

[0031] The purchased MWCNTs, purified MWCNTs and MWCNTs / Ni were characterized by SEM. The test results are as follows: Figure 1 shown. Figure 1 (a)~(c) are SEM photos of the purchased MWCNTs powder samples; (d)~(f) are SEM photos of the MWCNTs powder samples after purification by high-concentration HNO3 solution; (g)~(i) are SEM photos of MWCNTs / Ni powder samples. It can be observed from the figure that the purchased MWCNTs are more severely entangled, with protrusions on the surface of the tube wall and small particle clusters on some tube ends, while the surface of the MWCNTs purified by high-concentration HNO3 solution is relatively smooth, indicating that the purification treatment has achieved a good effect of removing impurities; Depend on Figure 1 (g) to (i) It can be clearly seen that the Ni coating is attached to the surface of MWCNTs, and the coating is evenly wrapped around the outside of the MWCNTs tube wall. The coating is continuous, flat and of uniform thickness, indicating that the growth advantage of Ni particles in the tangential direction is significantly greater than that in the normal direction. There is no large-scale aggregation and adhesion of Ni particles in the figure, and the outline of a single MWCNTs / Ni is clear and the dispersion is good. Ten points were randomly selected for EDS scanning, and the average Ni content in the sample was found to be 31.48%. In summary, the process scheme of the present invention can obtain MWCNTs / Ni powders suitable for subsequent steps.

[0032] The structural stability of the MWCNTs / Ni powder material obtained by the above processing steps is further enhanced during the sintering process. The MWCNTs / Ni was placed in a vacuum sintering device and kept at 1410°C for 40 minutes, with a heating rate of 10°C / min, and then cooled with the furnace. The morphological changes of the MWCNTs / Ni after sintering were observed by SEM. Figure 2 After sintering, a large number of Ni particles appear on the wall of MWCNTs tubes, which are uniformly dispersed and attached to MWCNTs. The particle size is significantly increased compared with that before sintering, and some carbon nanotubes form a structure of MWCNTs-Ni-MWCNTs overlapping each other. The tubular structure of the carbon nanotubes themselves is basically unchanged before and after sintering, and the end caps of very few carbon nanotubes become open, indicating that the carbon nanotubes can maintain structural stability under vacuum sintering below 1410°C and a holding time of less than 40 minutes. The MWCNTs / Ni of the present invention is used as a reinforcement of WC-8Co material. The preparation of MWCNTs / Ni-reinforced WC-based composite hard alloy material under vacuum sintering conditions of 1410°C can avoid the destruction of the carbon nanotube structure during the sintering process, and Ni is used as a bonding phase, and only the change in shape does not affect the strengthening of the alloy performance by MWCNTs.

[0033] Step 2: Add MWCNTs / Ni powder material to anhydrous ethanol in which JCCADS is dissolved, and the amount of dispersant added is 0.2 times the weight of carbon nanotubes. After 90 minutes of ultrasonic oscillation, centrifugal sedimentation, and filtration, an anhydrous ethanol dispersion system of MWCNTs / Ni is prepared. The precipitate separated by filtration is dried to a constant weight, and the mass of the dispersant in the precipitate is calculated by thermogravimetric measurement. The difference between the total mass of the precipitate and the mass of the dispersant in the precipitate is the mass of MWCNTs / Ni in the precipitate, and the difference between the total amount of MWCNTs / Ni added and the mass of MWCNTs / Ni in the precipitate is the content of MWCNTs / Ni in the dispersed solution after filtration.

[0034] Step 3: Add the MWCNTs / Ni anhydrous ethanol dispersion system to the WC-8Co cemented carbide powder for ball milling. The ball milling medium is anhydrous ethanol, the ball mill speed is 400 r / min, and the ball milling time is 50 h.

[0035] In this step, the addition amount of MWCNTs / Ni is 0.2-1% by weight, and the rest includes: 0.6% by weight of VC, 0.4% by weight of LC-38, 8% by weight of Co, and the balance is WC.

[0036] Step 4: After the ball milling is completed, the grinding balls and the slurry are separated by sieving through a sieve, and the slurry is placed in a vacuum drying oven at 70° C. for 1.5 h to obtain a mixed powder.

[0037] Step 5: Press and sinter the mixed powder to obtain WC-8Co cemented carbide; LC-38 is mixed before the mixed powder is pressed, and the specific pressing pressure is 210 MPa.

[0038] Mixing micro wax powder LC-38 into the alloy powder before powder pressing can reduce the friction between the powders, alleviate the uneven pressure transmission during pressing and the uneven density of different parts in the pressed green sheet, reduce internal stress and improve the quality of the pressed green sheet.

[0039] In the present invention, vacuum sintering is adopted, such as Figure 3 The figure shows the vacuum sintering curve. Below 1000℃ is the pre-sintering stage. During this stage, the residual stress of the preformed billet can be eliminated, and the negative pressure is drawn to volatilize the moisture, alcohol and gas in the block. The final sintering temperature is 1410℃, the holding time is 30min, and then the temperature is reduced to 150℃ at the rated cooling rate of the sintering furnace in each temperature zone. After that, the power is turned off and the furnace is cooled down. Finally, the sintered sample is taken out.

[0040] In step 3, the addition amount of MWCNTs / Ni is divided into six groups, namely 0 weight%, 0.2 weight%, 0.4 weight%, 0.6 weight%, 0.8 weight%, and 1.0 weight%; Six groups of alloy composite powders with different MWCNTs / Ni contents were observed by SEM. Figure 4 As shown in the figure: after ball milling and mixing of MWCNTs / Ni, WC powder, Co powder, VC powder and lubricating wax powder, the particle size of each group of mixed powders is larger than that of the raw material powder. This is because during the ball milling process, some fine particles of WC powder, Co powder, VC powder and MWCNTs / Ni are wrapped by the soft and larger particles of lubricating wax powder to form larger mixed particles.

[0041] pass Figure 5 (b) and (c) show that MWCNTs / Ni has a good dispersion effect in the composite powder, and MWCNTs / Ni is evenly mixed with WC-8Co cemented carbide powder, indicating that the MWCNTs / Ni dispersion prepared by mechanical stirring and ultrasonic oscillation has a good dispersion effect, and then by ball milling with WC-8Co composite powder, further dispersion and crushing in ball milling make MWCNTs / Ni further dispersed and fully mixed with WC-8Co composite powder, reducing the possibility of MWCNTs / Ni agglomeration. At the same time, after Ni plating, the density difference between MWCNTs and metal powder is reduced, making MWCNTs / Ni less likely to be stratified with WC-Co powder in ball milling compared with traditional MWCNTs, which is conducive to the uniform distribution of MWCNTs / Ni between powder particles. Figure 5 d ~ f are the states of MWCNTs / Ni in the mixed powder when the MWCNTs / Ni content is not less than 0.6 wt.%. When the MWCNTs / Ni content is 0.6 wt.%, MWCNTs / Ni agglomerates begin to appear in the mixed powder, but single dispersed MWCNTs / Ni can still be observed, indicating that the MWCNTs / Ni content is high at this time, and its state of existence begins to change from single dispersion to multiple agglomerations. Dispersed MWCNTs / Ni and MWCNTs / Ni agglomerates coexist in the mixed powder. When the MWCNTs / Ni content is higher than 0.6wt.%, larger MWCNTs / Ni agglomerates can be observed in the mixed powder. This mixed state not only cannot play the strengthening and toughening role of MWCNTs / Ni, but also will appear small gaps around the agglomerates. These small gaps cannot be filled by Co phase during sintering, thereby increasing the porosity of the cemented carbide matrix after sintering.

[0042] Figure 6 This is the SEM of the alloy microstructure after sintering. Figure 7 The statistical diagram of alloy grains in each combination. In general, the alloy grains remain at the nanoscale after sintering, with an average size of 398.1nm. The adhesion of fine powder particles by micro wax powder during ball milling does not affect the final WC grain size.

[0043] Depend on Figure 6(a) It can be seen that after sintering, the WC grain size of the WC-8Co cemented carbide without adding MWCNTs / Ni increases significantly relative to the raw material WC particle size, forming larger WC grains. There are generally two reasons for its formation. First, during the solid-phase sintering process, as the temperature increases, the contact area between the WC grains increases and finally gradually bonds into large grains; second, during the liquid-phase sintering process, some active and fine WC particles are first immersed in the liquid phase, and then precipitated on the surface of some WC particles near the liquid phase, causing the WC particles to grow slowly and eventually form the large WC particles shown in the figure.

[0044] from Figure 6 (b) It can be seen that the grain size of cemented carbide with 0.2 wt% MWCNTs / Ni is Figure 6 In (a), the cemented carbide grains without MWCNTs / Ni addition are finer, but Figure 6 (b) with Figure 6 Compared with (c), it can be seen that in the cemented carbide with the addition of 0.4 wt% MWCNTs / Ni, the WC grain size is not only relatively small, but also most of the WC grains are regular and uniform in shape. This shows that the addition of MWCNTs / Ni can indeed hinder the growth of WC grains and achieve the effect of grain refinement. It also proves that after vacuum sintering at 1410°C, MWCNTs / Ni can still stably exist in the cemented carbide and can continuously inhibit the growth of WC grains in both the solid / liquid phase sintering stages.

[0045] As a nano-reinforced phase, MWCNTs / Ni provides a large number of micro-interface regions in WC-8Co cemented carbide. These micro-interfaces provide more nucleation sites for WC during the sintering stage. At the same time, the presence of one-dimensional fibrous MWCNTs / Ni hinders the movement of the WC primary phase interface, which inhibits the growth of WC grains. The simultaneous action of the two ultimately makes the WC grains finer. Figure 6 (b) (c) (d) It can be seen that in the WC-8Co cemented carbide doped with 0.6 wt% MWCNTs / Ni, most of the grains are relatively small, but there are local discontinuous and abnormally enlarged WC particles. This is because the excessive doping of MWCNTs / Ni increases the possibility of their mutual agglomeration. The agglomerated MWCNTs / Ni will hinder the liquid phase infiltration during the liquid phase sintering stage and cause uneven liquid phase distribution. There will be a strong dissolution-precipitation effect in the liquid phase concentration area, which will cause the WC grains to increase abnormally and discontinuously. Figure 6 The average size of WC grains in (e) increases by 1.11% compared with that in (d), and the average size of WC grains in (f) increases by 2.15% compared with that in (e). The reasons are the same as above, that is, the degree of agglomeration of MWCNTs / Ni increases, which weakens its inhibitory effect on the growth of WC grains.

[0046] Figure 8 The figure shows the test of hardness and fracture toughness of WC-8Co alloy strengthened by MWCNTs / Ni. As shown in the figure, with the increase of MWCNTs / Ni content, the hardness of WC-8Co alloy strengthened by MWCNTs / Ni shows a slow downward trend. When adding 0.2wt.%~0.6wt.%MWCNTs / Ni, the hardness only decreases slightly, but when adding 0.8wt.%MWCNTs / Ni, the hardness value decreases by 2.60% relative to the hard alloy with 0.6wt.%MWCNTs / Ni content. The reason for the decrease in alloy hardness is that during the high-temperature sintering process, the more active C in the defects, defect-free but unplated Ni areas or sparsely plated areas on the MWCNTs tube wall obtains energy and migrates. The trace amount of rich C weakens the solid solution strengthening effect of W in Co, causing the hardness to decrease. When the MWCNTs / Ni content is too high, the rich C phenomenon is more obvious and the hardness decreases faster. The increase of C content will prolong the retention time of liquid phase during sintering of MWCNTs / Ni strengthened WC-8Co alloy, that is, the "dissolution-precipitation" effect mentioned above will be enhanced, which will cause abnormal growth of local grains in MWCNTs / Ni strengthened WC-8Co alloy. In addition, the agglomeration caused by the increase of MWCNTs / Ni content, the discontinuous growth of WC grains, and the uneven structure of cemented carbide will also reduce the hardness of the alloy. The fracture toughness of cemented carbide with 0.4 wt.% MWCNTs / Ni added reached 12.9 , the fracture toughness of the cemented carbide without MWCNTs / Ni was increased by 16.91%. The hardness of the cemented carbide with 1 wt.% MWCNTs / Ni was 4.31% lower and the fracture toughness was 9.92% lower than that of the cemented carbide without MWCNTs / Ni. The reason is that when the addition amount is too high, the bonding phase does not wet the carbon nanotubes completely, and the agglomeration and entanglement of the carbon tubes will be unfavorable to the completion of the densification process. In addition, due to the influence of trace impurities in the carbon nanotubes, the excessive carbon tubes form metallographic defects in the alloy structure. The fracture of the cemented carbide material starts from the defects inside or on the surface. Therefore, the fracture toughness of the alloy decreases when the MWCNTs / Ni content is too high.

[0047] Fig. 9The figure shows the detection data curve of the coercive force and grain size of the WC-8Co alloy strengthened by MWCNTs / Ni after sintering. From the figure, the coercive force curve increases first and then decreases. When the MWCNTs / Ni content is 0.4 wt%, the coercive force of the WC-8Co alloy strengthened by MWCNTs / Ni reaches a maximum value of 27.2 KA / m, which is 5.11% higher than that of the WC-8Co cemented carbide without adding MWCNTs / Ni. Under the condition of a certain proportion of Co bonding phase, the higher the coercive force, the thinner the thickness of the Co bonding phase, that is, the larger the spreading area, which indicates that the specific surface area of ​​the WC grains in the alloy is larger and the grains are finer, which is consistent with the grain size results calculated by the SEM metallographic image, and once again proves that MWCNTs / Ni has the effect of refining WC grains.

[0048] Fig.10 The figure shows the effect of MWCNTs / Ni content on the density and compactness of WC-8Co cemented carbide. It can be seen from the figure that when the addition of MWCNTs / Ni is not higher than 0.4 wt.%, the alloy density increases with the increase of the addition amount. When the addition amount of MWCNTs / Ni is between 0.6 and 1.0 wt.%, the alloy density decreases with the increase of the addition amount. The optimal addition amount is 0.4wt.%. The sintering method of the alloy in this paper involves liquid phase sintering. Liquid phase sintering is the process of continuous discharge of pores out of the blank. When the addition amount of MWCNTs / Ni is not higher than 0.4wt.%, the liquid phase can smoothly fill the microscopic pores by "capillary action" to increase the density of the alloy; when the addition amount of MWCNTs / Ni is higher than 0.4 wt.%, too much MWCNTs / Ni leads to inevitable agglomeration. More MWCNTs / Ni agglomerates exist between metal particles, which hinder the flow of the liquid phase during the sintering process, making the liquid phase incompletely wetted, which is not conducive to densification, and ultimately leads to a decrease in density.

[0049] Fig.11The figure shows the effect of MWCNTs / Ni content on the flexural strength of WC-8Co cemented carbide. The toughness of MWCNTs / Ni-reinforced WC-8Co alloy increases with grain refinement. At 0.4 wt% MWCNTs / Ni content, the flexural strength of MWCNTs / Ni-reinforced WC-8Co alloy reaches 2838MPa, which is 29.53% higher than the flexural strength of cemented carbide without MWCNTs / Ni addition. This shows that the use of MWCNTs / Ni composite WC-8Co cemented carbide material can achieve a good strengthening and toughening effect, and its mechanical properties are greatly improved. When the MWCNTs / Ni addition is not higher than 0.4 wt%, the flexural strength of the alloy increases with the increase of MWCNTs / Ni addition. When the MWCNTs / Ni addition is 0.4 wt%, the flexural strength of the MWCNTs / Ni-reinforced WC-8Co alloy reaches a maximum value of 2946MPa. Adding more than 1.0 wt% of MWCNTs / Ni easily causes agglomeration, which in turn reduces the flexural strength of the cemented carbide.

[0050] In summary, we can draw the following conclusions: After vacuum sintering, MWCNTs / Ni still exists in the WC-8Co alloy, inhibiting the movement of the primary interface, inhibiting the growth of WC grains and refining WC grains. In addition, the bonding strength between MWCNTs / Ni and the WC-8Co alloy matrix is ​​relatively high, and the excellent mechanical properties of carbon nanotubes can be used to enhance the performance of cemented carbide.

[0051] The coercive force of WC-8Co cemented carbide with a mass fraction of 0.4 wt% MWCNTs / Ni reaches the maximum, which is 6.82% higher than that of WC-8Co cemented carbide with a mass fraction of 0.0wt% MWCNTs / Ni. At this time, the alloy grains are the finest.

[0052] The hardness of cemented carbide decreases slightly with the increase of MWCNTs / Ni addition. When 0.4 wt% MWCNTs / Ni is added, the hardness of the alloy decreases by 0.34% compared with the hardness of the alloy without addition.

[0053] When the MWCNTs / Ni content exceeds 0.8 wt%, MWCNTs / Ni will be more likely to agglomerate, which will cause uneven distribution of Co phase in the liquid phase sintering stage of cemented carbide and discontinuous abnormal growth of WC grains, which will have an adverse effect on the properties of the alloy.

[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a carbon nanotube-reinforced cemented carbide, characterized in that: The following steps are involved: S1. preparing MWCNTs / Ni powder material; S2, adding MWCNTs / Ni powder material into anhydrous ethanol containing JCCADS, and obtaining MWCNTs / Ni anhydrous ethanol dispersion system after ultrasonic oscillation, centrifugal sedimentation and filtration; S3, adding the MWCNTs / Ni anhydrous ethanol dispersion system to WC-8Co cemented carbide powder for ball milling; S4, separating the grinding balls and the slurry by sieving, and vacuum drying the slurry to obtain a mixed powder; S5. Pressing and sintering the mixed powder to obtain WC-8Co cemented carbide.

2. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 1, characterized in that: In step S1, preparing MWCNTs / Ni powder material includes the following steps: S101, purifying MWCNTs using high concentration HNO3 solution; S102, putting the purified MWCNTs obtained in step S101 into a 10 g / L SnCl2 aqueous solution at pH=1, stirring, ultrasonically treating, washing, filtering and drying to obtain sensitized MWCNTs; S103, putting the sensitized MWCNTs into an activation solution, stirring, ultrasonically treating, washing, filtering and drying to obtain activated MWCNTs; S104, placing the activated MWCNTs obtained in step S103 into a chemical Ni plating solution, and plating for 100 minutes at a constant temperature; MWCNTs / Ni is separated from the aqueous solution and dried to obtain MWCNTs / Ni powder material.

3. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 2, characterized in that: In step S104, the pH of the plating solution is adjusted to 8.1 with (NH4)2SO4; Surfactant C is also added to the chemical Ni plating solution. 18 H 29 NaO3S, dosage is 0.1g / L.

4. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 2, characterized in that: In step S104, the MWCNTs / Ni is repeatedly washed with deionized water until it becomes neutral, and the MWCNTs / Ni and the aqueous solution are separated by a combination of centrifugation and suction filtration; The MWCNTs / Ni was completely dried at 170°C for 7 h.

5. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 2, characterized in that: In step S101, MWCNTs and high concentration HNO3 solution are added to a round-bottom flask, heated to 120°C in a condensation reflux device, and kept warm for 12 hours; The treated MWCNTs are then repeatedly washed with deionized water, filtered and separated after washing, and completely dried in a vacuum drying oven to obtain purified MWCNTs.

6. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 2, characterized in that: In step S103, the activation solution is a mixed solution with a pH of 1, and the solution composition is a PdCl2 solution with a concentration of 0.5 g / L and a H3BO3 solution with a concentration of 10 g / L.

7. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 1, characterized in that: The amount of dispersant added to the anhydrous ethanol in which JCCADS is dissolved is 0.2 times the weight of the carbon nanotubes.

8. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 1, characterized in that: In step S3, the addition amount of MWCNTs / Ni is 0.2-1% by weight, and the rest includes: 0.6% by weight of VC, 0.4% by weight of LC-38, 8% by weight of Co, and the balance is WC.

9. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 8, characterized in that: In step S5, LC-38 is mixed into the mixed powder before it is pressed.

10. The method for preparing a carbon nanotube-reinforced cemented carbide according to claim 1, characterized in that: In step S5, the pressing pressure is 210 MPa.